JURNAL KESEHATAN Kepuasan Pasien Pada Pelayanan Informasi Obat (PIO) Apotek Astu Putra Cawas Klaten PATIENT SATISFACTION WITH DRUG INFORMATION SERVICES (PIO) ASTU PUTRA PHARMACY CAWAS KLATEN - Rr. Erni Kusuma Putri (STIKES DUTAGAMA KLATEN, 2022)
Patient satisfaction is one of the benchmarks for assessing professional services from the quality of pharmaceutical services. This study aims to determine patient satisfaction with drug information services at the Astu Putra Pharmacy, Cawas, Klaten Regency based on the dimensions of service quality: responsiveness, assurance, empathy, and tangible reliability. The research method used is descriptive using a questionnaire given to 100 respondents. The data obtained from the questionnaire was calculated the average percentage of patient satisfaction and expectations and categorized. The results showed that patient satisfaction was based on the dimensions of service quality on the reliability dimensionwith the very satisfied category (81%), the responsiveness dimension with the satisfied category (77.4%), on the assurance dimensionthe satisfied category (77.8%) , dimensions of empathy (empaty) with a satisfied category (76.9%), and tangible (tangiable) with a satisfied category (75.7%). From the five dimensions, the percentage result is 77.76% in the satisfied category. While the results of respondents' expectations on the five dimensions obtained an average score of 85.98%, which means that patients feel hope is very important for improving pharmaceutical services at the Astu Putra Pharmacy, Cawas, Klaten Regency